The mirror reflects more for genial than for casual: right-asymmetry bias on the visual word recognition of words containing non-reversal letters - Soares, Ana Paula (2021)
Soares, Lages, Oliveira, and Cabrera-Hernández (2019) recently showed that the mirror-letter interference effect observed for words containing reversal letters was reliable for words containing left-oriented mirror-letters as ‘d’, but not for words containing right-oriented mirror-letters as ‘b’, thus indicating that the directionality of the reversal letters cannot be disregarded when examining the cost of suppressing the mirror-generalization mechanism at the early stages of visual word recognition. Here we examined whether this bias can also be observed for left-oriented non-reversal letters such as ‘g’, ‘j’, and ‘z’, which just as ‘d’ are also prone to errors in writing in left-to-right orthographies as European Portuguese (EP). Thirty-six EP skilled readers performed a lexical decision task combined with a masked-priming paradigm in which target words containing either left-oriented (e.g., ‘g’, genial) or right-oriented (e.g., ‘c’, casual) non-reversal letters were preceded by 50 ms primes that could be the same as the target (genial–genial, casual–casual), nonword primes in which the critical letter was replaced by the mirror-image of the left- or rightoriented non-reversal letter ( enial–genial, asual–casual), or nonword primes in which the critical letter was replaced by the mirror-image of another left-oriented or right-oriented non-reversal letter as control ( enial-genial, asual-casual). Results showed that the amount of priming produced by identity primes and mirror-image primes was virtually the same for words with left-oriented (e.g., genial–genial = enial–genial), but not for words with right-oriented non-reversal letters (e.g., casual–casual > asual–casual), hence extending the right-oriented bias observed for words containing reversal letters to words containing non-reversal letters.